Financial Deepening & Income Inequality: Evidence From Indonesia - Alghifari Mahdi Igamo; Gustriani Gustriani; Sri Maryati; Azwardi Azwardi; Sukanto Sukanto (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2023)
Financial deepening is a term used to measure the quality of improvement in the provision of financial services. Financial deepening can be seen as one of the factors affecting income inequality. The focus of financial deepening in this research using a credit ratio is a ratio of total credit released by commercial banks in each province compared to the province’s GDP and the bank ratio is the ratio of the number of bank branches per million population of the province. The discussion of this research is limited to using country data from 34 provinces in Indonesia from 2005-2021. The results show that the various indicators that measure financial deepening have an impact on increasing inequality during the observation period. This condition shows that financial services, especially banking access through the ratio of the number of banks and also the development of the credit ratio, have not been able to reduce income inequality. The government needs to evaluate policies and improve the quality of sustainable financial services to achieve a more even distribution of income so that income inequality can be reduced.